Safety and medical cost effectiveness of preventive treatment of children with latent tuberculosis infection - O. D. Baronova; V. A. Aksenova; N. I. Klevno; V. S. Odinets; O. V. Pilipenko (Туберкулез и болезни лёгких)
The objective: to assess the safety and medical cost effectiveness of different LTBI treatment regimens in children and adolescents.Subjects and methods. 205 children in the age from 6 to 17 years old with latent tuberculosis infection were included in the study: The main (prospective) group included 31 children who were treated with isoniazid and rifapentine (HRpt). The comparison (retrospective) group included 174 pediatric patients: 128 patients received the regimen consisting of isoniazid and pyrazinamide (HZ), 14 patients received isoniazid and rifampicin (HR), and 32 patients received isoniazid and ethambutol (HE).Results. When using the HRpt regimen, the treatment was well tolerated; adverse events (eosinophilia) were documented in 6.5% of children. The medications were taken once a week and it allowed reducing the frequency of treatment interruptions for non-medical reasons. The overall cost per patient was lower with the HRpt regimen than with the other three LTBI treatment regimens.